"Get drunk. Smoke weed. Have fun.": A Content Analysis of Tweets About Marijuana and Alcohol. Issue 3 (May 2017) - Krauss, Melissa J.; Grucza, Richard A.; Bierut, Laura J.; Cavazos-Rehg, Patricia A.
Purpose: To explore the sentiment and themes of Twitter chatter that mentions both alcohol and marijuana. Design: Cross-sectional analysis of tweets mentioning both alcohol and marijuana during 1 month was performed. Setting: The study setting was Twitter. Participants: Tweets sent from February 4 to March 5, 2014, were studied. Method: A random sample (n = 5000) of tweets that mentioned alcohol and marijuana were qualitatively coded as normalizing both substances, preferring one substance over the other, or discouraging both substances. Other common themes were identified. Results: More than half (54%) of the tweets normalized marijuana and alcohol (without preferring one substance over the other), and 24% preferred marijuana over alcohol. Only 2% expressed a preference for alcohol over marijuana, 7% discouraged the use of both substances, and the sentiment was unknown for 13% of the tweets. Common themes among tweets that normalized both substances included using the substances with friends (17%) and mentioning substance use in the context of sex or romance (14%). Common themes among tweets that preferred marijuana over alcohol were the beliefs that marijuana is safer than alcohol (46%) and preferences for effects of marijuana over alcohol (40%). Conclusion: Tweets normalizing polysubstance use or encouraging marijuana use over alcohol use are common. Both online and offline prevention efforts are needed to increase awareness of the risks associated with polysubstance use and marijuana use.